Arts and Culture Education in Bali Urban Sketchers Community Activities: A Netnographic Study Perspective - Adipurwa, Anak Agung Trisna Ardanari; Udiyana Wasista, I Putu; Resi Kerdiati, Ni Luh Kadek; Ari Darmastuti, Putu (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2023)
Urban Sketchers Bali (USK Bali) is a community engaged in capturing life's moments in the surrounding environment through sketches. Cultural moments become objects most often used as sketches. In the process, USK Bali members come from various professional backgrounds, from artists to those without an artistic background. Then there is an interesting phenomenon in transferring knowledge about art and culture. USK Bali members do not have a professional educator background, but the learning process and learning climate are conducive and enjoyable. The purpose of this study is to see the educational process that occurs both in its interactions and strategies. This research is qualitative with a netnographic approach, which summarizes and analyzes a sample of interactions on social media. The result is that naturally and instinctively, the educational process that is formed already uses four approaches in education: behavioristic, cognitivist, constructivist, and humanist. This process shows that in the spontaneous transfer of knowledge, someone already has all of these approaches even though they do not have a professional educator background.